Effectiveness of lemon essential oil in reducing test anxiety in nursing students - Ozer, Zulfinaz; Teke, Neslihan; Turan, Gulcan Bahcecioglu; Bahcecik, Ayse Nefise (Elsevier Science Inc, 2022)
Purpose: This study examines the effectiveness of lemon essential oil in reducing test anxiety in first-year nursing students. Method: A randomized, pre-test-post-test design was used in this study. The study included 46 first-year students from the Faculty of Medical Sciences of a private university in Istanbul, Turkey. Students were divided into two groups through randomization (Intervention, N = 22; Control, N = 24). In the pre-test, a personal information form, State Test Anxiety Scale (STAS) and Test Anxiety Schedule (TAS) were administered to students in both groups. The students in the intervention group smelled lemon essential oil for 15 min. The study was completed by applying STAS and TAS as post-test. Results: After smelling lemon essential oil, a significant difference was found between the mean pre-test and post-test scores for STAS, its sub-dimensions and TAS (p < 0.01) in the intervention group. It was observed that the nursing students' mean scores for STAS, its sub-dimensions and TAS decreased after smelling lemon essential oil (p <0.05). It was found that the intervention group's mean post-test scores for STAS, cognitive sub-dimension and TAS were lower than those of the control group. Mean post-test scores of physiological sub-dimension in the intervention group were also significantly lower than the control group. It was concluded that lemon essential oil reduced test anxiety by 43.3%. Conclusion: Lemon essential oil was found to be effective in reducing test anxiety in nursing students. (C) 2022 Elsevier Inc. All rights reserved.
Keywords: Lemon essential oil; Test anxiety; Student; Nurse